1991
DOI: 10.1017/s003329170002239x
|View full text |Cite
|
Sign up to set email alerts
|

The pathways to psychiatric care: a cross-cultural study

Abstract: SYNOPSIS This paper describes the referral pathways taken by 1554 patients newly referred to the mental health services in 11 countries, and documents factors associated with delays in referral. The pathways in centres relatively well provided with psychiatric staff were dominated by general practitioners and to a lesser extent hospital doctors: the relatively less well resourced centres showed a variety of pathways with native healers often playing an important part. Delays were remarkably short in all centre… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

13
224
5
8

Year Published

1993
1993
2019
2019

Publication Types

Select...
7
2

Relationship

0
9

Authors

Journals

citations
Cited by 259 publications
(255 citation statements)
references
References 4 publications
(2 reference statements)
13
224
5
8
Order By: Relevance
“…We therefore used an amended version of the encounter form from Gater et al 75 in which an interview and coding protocol were created to ensure consistency between researchers (see Appendix 8). As with the NOS, all medical notes and correspondence are collated into a timeline detailing the patient's journey to psychiatric care.…”
Section: Illness Encounters and Pathways To Carementioning
confidence: 99%
“…We therefore used an amended version of the encounter form from Gater et al 75 in which an interview and coding protocol were created to ensure consistency between researchers (see Appendix 8). As with the NOS, all medical notes and correspondence are collated into a timeline detailing the patient's journey to psychiatric care.…”
Section: Illness Encounters and Pathways To Carementioning
confidence: 99%
“…Two studies reported using semi-structured questionnaires (Cole et al, 1995, Cougnard et al, 2004) and one reported simply asking patients for information on their contacts with professionals before admission and their pathways to care (Fuchs and Steinert, 2004). One study used the Encounter Form (Gater et al, 1991) and two others based their measures on other assessment tools (Etheridge et al, 2004, Norman et al, 2004; one on the IRIS audit tool kit (Partnerships, 2001) and the other, the Circumstances of Onset and Relapse Schedule (CORS) which is based on the Interview for the Retrospective Assessment of Schizophrenia (IRAOS) (Hafner et al, 1992). One study gathered data on pathways to care using qualitative techniques i.e.…”
Section: Pathways Measure Usedmentioning
confidence: 99%
“…In this study, somatic problems were found to be the most common initial presenting problem, and the majority of the patients had previously received some form of treatment for their present problem. 62 The proportion of patients with depressive disorders across centers was comparable. Contrary to what is often reported, somatic complaints were not more frequent in developing countries.…”
Section: No3 Mayo-junio De 1999mentioning
confidence: 93%
“…In addition, the study uncovered that recognizing depression by the physician does not mean that the patient will be provided with treatment, as only half were offered a drug treatment. 61,62 …”
Section: Pathways To Mental Health Carementioning
confidence: 99%